2017
DOI: 10.18632/oncotarget.16309
|View full text |Cite
|
Sign up to set email alerts
|

The TERT rs2736100 polymorphism increases cancer risk: A meta-analysis

Abstract: Abnormal telomerase activity is implicated in cancer initiation and development. The rs2736100 T > G polymorphism in the telomerase reverse transcriptase (TERT) gene, which encodes the telomerase catalytic subunit, has been associated with increased cancer risk. We conducted a meta-analysis to more precisely assess this association. After a comprehensive literature search of the PubMed and EMBASE databases up to November 1, 2016, 61 articles with 72 studies comprising 108,248 cases and 161,472 controls were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 87 publications
(46 reference statements)
0
20
0
2
Order By: Relevance
“…The rs2736100_C allele of the TERT gene was previously shown to be associated with an elevated risk for several other neoplasia, such as glioma, lung and bladder cancers ( Figure 1 ) [ 35 , 36 , 37 , 38 ]. A recent meta-analysis confirmed that the TERT rs2736100 polymorphism is associated with increased overall cancer risk, including solid cancers, myeloproliferative neoplasms, and acute myeloid leukemia [ 39 ]. The JAK2 haplotype GGCC_46/1 and TERT rs2736100_C are independent factors predisposing to MPN and confering an additional disease risk ( Figure 1 ) [ 22 , 27 , 40 , 41 ].…”
Section: The Role Of the Jak2 Haplotype mentioning
confidence: 99%
See 1 more Smart Citation
“…The rs2736100_C allele of the TERT gene was previously shown to be associated with an elevated risk for several other neoplasia, such as glioma, lung and bladder cancers ( Figure 1 ) [ 35 , 36 , 37 , 38 ]. A recent meta-analysis confirmed that the TERT rs2736100 polymorphism is associated with increased overall cancer risk, including solid cancers, myeloproliferative neoplasms, and acute myeloid leukemia [ 39 ]. The JAK2 haplotype GGCC_46/1 and TERT rs2736100_C are independent factors predisposing to MPN and confering an additional disease risk ( Figure 1 ) [ 22 , 27 , 40 , 41 ].…”
Section: The Role Of the Jak2 Haplotype mentioning
confidence: 99%
“…In this hypothesis, the haplotype GGCC_46/1 could provide a global DNA propensity for gene mutations and MPN development, as some conflicting evidence indicates that this haplotype could also be associated to MPL or CALR gene mutations [ 16 , 17 , 22 , 62 ]. Moreover, this second hypothesis could explain the unclear observations that the haplotype may also be enriched in individuals with JAK2 V617F negative MPNs [ 7 , 12 , 13 , 19 , 20 , 39 ]. The “fertile ground hypothesis” could also explain the acquisition of mutations in other genes that are critical for expansion and differentiation of myeloid cells, possibly causing malignant transformation to MPN or AML [ 13 ].…”
Section: Potential Mechanisms Explaining the Association Between Tmentioning
confidence: 99%
“…ERCC1 is found to be associated with multiple cancers. ERCC1 variants have also been linked to an increased risk of BC (29) in women. The variant rs2298881 C>A was found signi cantly associated with breast cancer.…”
Section: Network Analysismentioning
confidence: 99%
“…Recently, genes involved in telomere length have been implicated in the pathogenesis of a variety of chronic lung diseases (CLDs), including IPF, COPD, and lung cancer (Alder et al, 2011;Codd et al, 2013;Fingerlin et al, 2013;Gansner and Rosas, 2013;Snetselaar et al, 2015;Stanley et al, 2015;Zhou and Wang, 2016). Mutations in the telomerase complex, TERT (telomerase reverse transcriptase) and TERC (telomerase RNA component), which help maintain telomere lengths and chromosome stability in cells, are of great importance to human health (O'Reilly et al, 1999;Ly, 2009) and has been reported as a risk of COPD (Ding et al, 2019), IPF (Noth et al, 2013;Kropski et al, 2015) and lung cancer (Fernandez-Garcia et al, 2008;Li et al, 2017). OBFC1 (oligosaccharidebinding fold-containing protein 1) is part of the CST complex (consists of CTC1, STN1, and TEN1 proteins), which binds to single-stranded DNA and is important for telomere maintenance (Levy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%